2007
DOI: 10.1186/1477-7827-5-14
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin expression and bromodeoxyuridine incorporation during development of ovarian inclusion cysts in age-matched breeder and incessantly ovulated CD-1 mice

Abstract: Background: Female CD-1/Swiss Webster mice subjected to incessant ovulation for 8 months and 12-month breeder mice both developed ovarian inclusion cysts similar to serous cystadenomas. The majority of cysts appeared to be dilated rete ovarii tubules, but high ovulation number resulted in more cortical inclusion cysts. We hypothesized that comparison of inclusion cyst pathology in animals of the same age, but with differences in total lifetime ovulation number, might allow us to determine distinguishing charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…Similar phenotypes have been observed in aged mice, transgenic mice, and ovarian diseases mouse models [3941]. Specifically, one study showed that CD-1 mice develop ovarian inclusion cysts starting at 6 months of age, but enlarged ovarian cysts were observed in a 9 month old animal [39]. In a transgenic mouse model with conditionally activated Notch1, enlarged ovarian cysts developed in 8 month old animals [40].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar phenotypes have been observed in aged mice, transgenic mice, and ovarian diseases mouse models [3941]. Specifically, one study showed that CD-1 mice develop ovarian inclusion cysts starting at 6 months of age, but enlarged ovarian cysts were observed in a 9 month old animal [39]. In a transgenic mouse model with conditionally activated Notch1, enlarged ovarian cysts developed in 8 month old animals [40].…”
Section: Discussionsupporting
confidence: 52%
“…The presence of ovarian cysts is often a sign of reproductive aging [38]. Similar phenotypes have been observed in aged mice, transgenic mice, and ovarian diseases mouse models [3941]. Specifically, one study showed that CD-1 mice develop ovarian inclusion cysts starting at 6 months of age, but enlarged ovarian cysts were observed in a 9 month old animal [39].…”
Section: Discussionmentioning
confidence: 84%
“…Some authors have suggested a secretory function of the rete ovarii in adults because secretory materials were observed in the lumen of the rete ovarii, which showed cystic changes in various species such as the cow, camel, cat, dog, and guinea pig (Byskov, 1975;Jiang et al 2004). Furthermore, some researchers have hypothesized that the rete ovarii is a common source of ovarian cysts and epithelial tumors in aged mice (Tan & Fleming, 2004;Tan et al 2005;Burdette et al 2007;Fleming et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported a high incidence of ovarian cysts derived from the rete ovarii in the MRL ⁄ MpJ (MRL) mouse strain, a representative model for autoimmune diseases, including dermatitis, vasculitis, arthritis, and glomerulonephritis (Ichii et al 2008;Kon et al 2008). Ovarian cysts in CD-1 mice, another model for rete-derived ovarian cysts, showed epithelial malformations of cysts such as hyperplasia, metaplasia, stratification, and the appearance of lengthened columnar cells with compact cilia or vacuolated cytoplasm (Long, 2002;Fleming et al 2007). In contrast, the rete ovarian cysts of MRL mice showed dilation of the IR, which is mainly lined with a single-layered ciliated or non-ciliated squamous or cuboidal epithelium (Kon et al 2008), with considerably fewer pathological changes than the IR epithelium of CD-1 mice described by Long (2002).…”
Section: Introductionmentioning
confidence: 99%
“…The histologic sections of the ovaries revealed an anovulatory phenotype; 5 of the 9 (55%) T-injected mice lacked a corpus luteum ( Table 2). Although epithelial inclusion cysts, which are commonly seen in old female mice (38), were observed in both T-injected and vehicle-treated mice, the T-injected mice had a higher frequency of epithelial inclusion cysts (55%) than CON mice ( Table 2). Although epithelial inclusion cysts, which are commonly seen in old female mice (38), were observed in both T-injected and vehicle-treated mice, the T-injected mice had a higher frequency of epithelial inclusion cysts (55%) than CON mice ( Table 2).…”
Section: Cyclicity and Ovarian Morphology (Table 2 And Figure 2)mentioning
confidence: 99%